МАКЕДОНСКОЕ ПРОСВЕТИТЕЛЬСТВО В БАЛКАНСКОМ КОНТЕКСТЕ (Filološke pripombe, 2019)
The Enlightenment created the political life, crystallized the form of creating a state, set the basis through the development of the army, the finances, the administration and the diplomacy. The state took on the rational aims: the education, the science, the authority over the church. The idea of enlightenment on the Balkan started in 19 century. In Macedonia, the Macedonian civil class (merchants and craftsmen) started the struggle against the Hellenism, the struggle for independent church and introduction of the vernacular in the schools, the struggle for development of the civil consciousness and inducement of the Macedonian national consciousness. After their initiative the church-school communities were created, which became the essence of the enlightenment. Supporters of the idea of enlightenment in Macedonia were the authors of textbooks, collectors of the folk literature, printers, representatives of the literature of the enlightenment (philosophical popular writings, moral weekly newspapers, edifyingentertaining magazines, pamphlets, calendars, student debates, human documents, memorys, chronicles, travels were written), representatives of the art (carvers, wood carvers, icon-painters) and representatives of the musical culture (the first melographs).